Optical and Morphological Properties of ZnO- and TiO2-Derived Nanostructures Synthesized via a Microwave-Assisted Hydrothermal Method - Nosipho Moloto; Siyasanga Mpelane; Lucky M. Sikhwivhilu; Suprakas Sinha Ray (International Journal of Photoenergy)
A microwave-assisted hydrothermal method was used to synthesize ZnO and TiO2 nanostructures. The experimental results show that the method resulted in crystalline monodispersed ZnO nanorods that have pointed tips with hexagonal crystal phase. TiO2 nanotubes were also formed with minimum bundles. The mechanism for the formation of the tubes was validated by HRTEM results. The optical properties of both ZnO and TiO2 nanostructures showed characteristics of strong quantum confinement regime. The photoluminescence spectrum of TiO2 nanotubes shows good improvement from previously reported data.